PENGARUH STRUKTUR PENGENDALIAN INTERNAL, TATA KELOLA DAN ANALISIS RISIKO KEUANGAN TERHADAP EFEKTIVITAS PENYALURAN KREDIT PADA KOPERASI SIMPAN PINJAM DI KABUPATEN ACEH BESAR - Suci hariyati; Fazli Syam BZ; Jhon Andra Asmara (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
The purpose of this study was to determine the effect of internal control structures, governance, and financial risk analysis on the effectiveness of credit distribution to savings and loan cooperatives in Aceh Besar District. The data used in this study are primary data using a quantitative approach. This study uses purposive sampling method in determining the sample, and there are 10 cooperatives that become samples that meet the criteria.Based on the research results, it shows that the structure of internal control, governance, and financial risk analysis together has a significant effect on the effectiveness of lending. The magnitude of the influence of internal control, governance and financial risk analysis on the effectiveness of lending was 63.8%. The internal control structure has a significant effect on the effectiveness of lending. Governance does not have a significant effect on the effectiveness of lending. Financial risk analysis has no significant effect on the effectiveness of lending